2012
DOI: 10.1111/j.1365-2095.2012.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility coefficients of selected feed ingredients for juvenile snakehead,Ophiocephalus argus

Abstract: Apparent digestibility coefficients (ADCs) of dry matter, crude protein, crude lipid, gross energy, phosphorus and amino acids in Peruvian fish meal, poultry by-product meal, meat and bone meal, spray-dried blood meal, hydrolysed feather meal, corn gluten meal, soybean meal, peanut meal, cottonseed meal and rapeseed meal were determined for juvenile snakehead (Ophiocephalus argus) with initial mean body weight of 78.1 g. A reference diet and test diets that consisted of a 70 : 30 mixture of the reference diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
5
18
0
1
Order By: Relevance
“…Similar results have also been observed in rainbow trout (Oncorhynchus mykiss) (Bureau et al 1999) and hybrid tilapia (O. niloticus × Oreochromis aureus) (Zhou and Yue 2012). The protein quality of the dietary ingredients is usually the leading factor affecting fish performance and protein digestibility and is the first measure of its availability for fish (Yu et al 2013). The ADC of protein in this study revealed that the protein of HM, MM, SM-A, and PM-A must be highly digestible by olive flounder.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Similar results have also been observed in rainbow trout (Oncorhynchus mykiss) (Bureau et al 1999) and hybrid tilapia (O. niloticus × Oreochromis aureus) (Zhou and Yue 2012). The protein quality of the dietary ingredients is usually the leading factor affecting fish performance and protein digestibility and is the first measure of its availability for fish (Yu et al 2013). The ADC of protein in this study revealed that the protein of HM, MM, SM-A, and PM-A must be highly digestible by olive flounder.…”
Section: Discussionsupporting
confidence: 68%
“…In the present study, lipid digestibilities were considered to be high (>90 %), except for PM-B (83 %). Previous studies reported ADC values of lipid in different fish meals including Peruvian fish meal (94 %) for juvenile snakehead, O. argus (Yu et al 2013); white fish meal (78 %); and brown fish meal (76 %) for loach, Misgurnus anguillicaudatus (Chu et al 2015). The digestibility of lipids is known to be influenced by a number of factors, including degree of unsaturation, dietary lipid level, and various other constituents (Yuan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aurata was investigated at that FM replacement level (50%) that was considered the breaking point in terms of successful replacement. The similarities in trypsin and chymotrypsin activities between PBM‐ and FM‐fed fish indicate the relatively high digestibility of a high‐quality PBM protein, comparable to that of FM, as it has been shown in many fish species (Hernández et al., ; Yu et al., ) and in S . aurata (Alexis, ; Davies et al., ; Nengas et al., ).…”
Section: Discussionmentioning
confidence: 56%
“…In general, PBM contains 450–650 g/kg protein and is rich in most essential amino acids, except lysine and methionine (González‐Rodríguez et al., ; Zhou, Zhao, Li, Wang, & Wang, ). In addition, its protein digestibility, although known to be variable and affected by the raw material (Nengas, Alexis, & Davies, ), has proven to be very high in various carnivorous fish species (Hernández et al., ; Yu et al., ), including gilthead seabream ( Sparus aurata , Lupatsch, Kissil, Sklan, & Pfeffer, ; Davies, Gouveia, Laporte, Woodgate, & Nates, ).…”
Section: Introductionmentioning
confidence: 99%